Smart material actuated autonomous snake robot - Md. Masum Billah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Snakes are available all over the world and the flexible biological structure allows snakes to roam over wide range of terrain without facing any difficulty. This especial feature of snake attracted researchers to mimic snake like robots. All the existing snake robots are made of rigid links, which are connected with joints of single degree of freedom. Electrical motors are commonly used as actuators for actuating these joints. Such actuation systems are not suitable for executing versatile snake motion due to their limitations of one degree of freedom. New kind of joints capable of executing two (2D) or three degree (3D) of freedom is a requirement to mimic natural snake locomotion. However, the traditional actuators like electrical motors that are popular in designing snake robots are not able to actuate such 2D or 3D joints. In this research, a new kind of 3D joint has been designed and used to develop a flexible snake robot. As electrical motors are not able to handle this multi-degree of freedom joints, Smart (active) materials in the form of tendons have been used for actuating these new joints. This approach has reduced the complexity of the controller that is developed for executing snake locomotion. A Central Pattern Generator (CPG) based motion control has been implemented for the motion control of the snake robot. The CPG based algorithm was adopted from gait analysis of real snake. The newly developed snake robot is capable of executing 3D motion, and executing online gait transition for obstacle avoidance. The snake robot was tested on three different surfaces possessing three different coefficients of friction. It was found that the maximum speed was achieved with the highest coefficient of friction. The maximum speed of the robot achieved was 2.0 cm per second on the surface of coefficient of friction of 0.46. Head rise of the robot achieved was 4 cm. Though smart materials made the snake robot capable to execute 3D motion, however, due to the limitation of actuation force high speed could not be achieved for the relatively heavy structure of the snake. Head rise of the robot also faced similar limitation. Further study on optimizing size of robot and smart actuator is expected to provide snake robot for real life application.